DETEKSI DAN KARAKTERISASI GEN HEMOLISIN (hlyA) Aeromonas hydrophila DAN PREDIKSI EPITOP SEL T DAN B PADA IKAN GURAMI (Osphronemus gouramy) - Raden Roro Salma Hayaah Megantari; Rozi Gunanti Mahasri (Universitas Mataram, 2026)
In 2050, fish consumption in Indonesia will continue to increase, with a target of 59 kg/capita by 2024. Gourami fish is one of the main commodities, but the problem faced is that it is susceptible to disease, especially due to Aeromonas hydrophila, the cause of Motile Aeromonas Septicemia (MAS). This bacteria is a toxin pathogen that damages fish tissue. The pathogenesis of A. hydrophila involves enzymes and toxins such as hemolysine (hlyA). Hemolysin can lyse red blood cells, cause necrosis and increase bacterial virulence. Control can be carried out organically or inorganically. Bioinformatics-based vaccines are a potential solution by targeting the hemolysin gene, which plays a role in bacterial virulence. This research is a descriptive laboratory and observational research. Samples were taken from fish suspected of being infected with MAS and analyzed through bacterial isolation, purification, and biochemical tests. After that, the bacterial DNA is extracted, then the hemolysin gene is amplified using PCR with a specific primer. PCR results were analyzed through electrophoresis, then sequenced using the Sanger method. Homological analysis was performed with BLAST, while phylogenetic relationships were mapped using MEGA11. Prediction of immunogenic epitopes is carried out with bioinformatics devices such as IEDB. The results showed the detection of the hlyA gene through the PCR method resulted is 592 bp. Homology analysis of isolate GGBS3 A. hydrophila has a similarity rate of 98%-100% with 7 strains from GenBank. Phylogenetic analysis showed a close relationship with the GenBank database of strains from India and China with a genetic distance of 0.98 (98%). Epitope prediction resulted in seven best candidates for B cells, as well as 30 epitopes for MHC II and 10 epitopes for MHC I that are non-allergenic, antigenic, non-toxic, and water-soluble.